(3efGbH GdCHQGQ heMGSf GdCNjGQs - (3GdMSjf Hf fUQ, ef Hfj NejS GdcYHqj GdehUdqj GdLgfqj , GpHf nNpejS,J (B552 (3g` s ((3GdMGL ebHd Hf YHOGddg YJjb GdMGL eMeO Hf YKeGf s)
(3ChdgG (B:s
(3CeG HYO , aEfi JJHYJ eSehYGJj eeG LeYg GdSGOI ef CNHGQ GdUGdMjf hCNHGQ GdChdjGA GdUGOb s
(3BNQgG (B:s
(3hgPG BNQ eG hbY ef EVGaGJ CNHGQ LeGYI ef GdUGdMjf QVi Gddg Yfge CLeYjf aCdMbJg HGdcJGH s
(3fSNI KGfjI JNJda aj ChdgG hBNQgG Yf GdfSNI GdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B261 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B66s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B434 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B776 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B419 s
Keywords: (3GdJGQjNs